Situation Report: Hungary, 3 December 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. News Manipulation Attacked by Prominent Writer Consumer Price Increases Mitbestimmung Hungarian Style? Contacts with Third World Countries US Secretary of Agriculture Visits Hungary Small Machines Needed by Private Plots Remain in Short Supply